Suicidality and Its Associated Factors Among Students in Rural China During COVID-19 Pandemic: A Comparative Study of Left-Behind and Non-Left-Behind Children - Hou, Tianya; Mao, Xiaofei; Shao, Xiaoqin; Liu, Fen; Dong, Wei; Cai, Wenpeng (Frontiers in Psychiatry, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) has rapidly spread worldwide. The harmful impact of COVID-19 is beyond just physical health concern. The unprecedented public health crisis has also taken its toll on mental health of the adolescents. The present study aims to estimate the prevalence of suicidal ideation and attempts, and investigate the similarities and differences in the influential factors for suicidal ideation and attempts among left-behind children (LBC) and non-left-behind children (NLBC) in rural China during COVID-19 pandemic. Method: A total of 761 rural Chinese students, of whom 468 were left-behind, completed the cross-sectional questionnaires including demographic data, Cognitive Emotion Regulation Questionnaire, 9-item Patient Health Questionnaire, 7-item Generalized Anxiety Disorder Scale, suicidal ideation and suicidal attempts. Chi-square test, independent-sample t test and logistic regression were performed in the statistical analysis. Results: Overall, 36.4% and 10.4% of rural Chinese students reported suicidal ideation (37.8% for LBC versus 34.1% for NLBC) and attempts (11.3% for LBC versus 8.9% for NLBC) during COVID-19 pandemic. Among LBC, parental educational level (Adjusted Odds Ratio (Adj.OR) =1.60), maladaptive strategies (Adj.OR=1.04), anxious symptoms (Adj.OR=2.61) and depressive symptoms (Adj.OR=3.85) were significantly associated with suicidal ideation, while age (Adj.OR=0.56), maladaptive strategies (Adj.OR=1.08), symptoms of anxiety (Adj.OR=3.85) and symptoms of depression (Adj.OR=2.68) were significantly related to suicidal attempts during COVID-19 outbreak. Among NLBC, gender (Adj.OR=2.20), parental educational level (Adj.OR=1.77), perceived family economic status (Adj.OR=0.39), anxious symptoms (Adj.OR=2.38) and depressive symptoms (Adj.OR=2.77) were significantly associated with suicidal ideation, whereas only anxious symptoms (Adj.OR=5.85) was significantly related to suicidal attempts. Conclusion: The suicidal ideation and attempts are prevalent among students in rural China during COVID-19 outbreak. Our findings also revealed the shared and unique factors for suicidal ideation and attempts among LBC and NLBC during COVID-19 epidemic. With regard to the differences between LBC and NLBC, the use of maladaptive strategies and age might be vital factors for suicide-prevention measures directed specifically towards LBC, whereas interventions sensitive to gender and perceived social economic status should be specifically designed for NLBC amid the COVID-19 pandemic.